The Influence of Trichocompost and NPK Fertilizer Combination on Productivity and Quality of Pakchong Grass - Lestari, Novita; Apriliana, Anisa Dwi; Liman, Liman; Erwanto, Erwanto; Muhtarudin, Muhtarudin (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This research aims to determine effect of applying a combination of trichocompost fertilizer and NPK fertilizer with different levels on the productivity of Pakchong grass. This research was conducted from October to December 2023 at the Integrated Field Laboratory Greenhouse, Faculty of Agriculture, University of Lampung. This study used a factorial completely randomized design (CRD) consisting of trichocompost and NPK fertilizer factors. The trichocompost fertilizer factor consisted of 4 treatment levels, namely T0: without trichocompost (control), T1: 15 tons/ha of trichocompost fertilizer, T2: 30 tons/ha of trichocompost fertilizer, and T3: 45 tons/ha of trichocompost and the NPK fertilizer factor consists of 4 treatment levels, namely K0: no NPK fertilizer (control), K1: 100 kg/ha urea + 50 kg/ha TSP + 50 kg/ha KCL, K2: 150 kg/ha urea + 75 kg/ha TSP + 75 kg/ha KCL, and K3: 200 kg/ha urea + 100 kg/ha TSP + 100 kg/ha KCL. The data obtained were analyzed using Analysis of Variance (ANOVA) and followed by the Least Significant Difference (LSD). The results showed that the combination of trichocompost and NPK fertilizer did not give a significant interaction (P>0.05) on the number of tillers, fresh weight and dry matter of pakchong grass, but had a significant effect (P<0.05) on fresh weight and dry matter of pakchong grass crown. The results of the LSD test on fresh weight and dry matter of pakchong grass showed that T3 trichocompost fertilizer treatment gave the best results when compared to other treatments. The results showed that the use of NPK fertilizer had a significant effect (P<0.05) on the crude protein content and crude fiber content of pakchog grass. The results of the LSD test on crude protein showed that K3 treatment provides the best results compared to other treatments. While the crude fiber content of K3 treatment was significantly different from K1.